Optimalisasi Jaringan untuk Meningkatkan Kinerja UKM Agroindustri Jawa Tengah di Pasar Dunia - Rozak, Hasan; Hadi, Arman; Rosyada Fitriati, Ika; Maelana, Herman; Dwi Hapsari, Paskalista (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Agroindustry SMEs in Central Java face significant challenges in competing in the global market. This study aims to explore the role of network capability in improving the performance of agroindustry SMEs in the international market. Using the Dynamic Capability Theory, this study shows that effective networking helps SMEs build strategic business relationships, gain market insights, and enhance global competitiveness. A survey of 123 SMEs in Central Java reveals that network capability plays a crucial role in improving  international market performance, particularly in terms of export sales, profitability, and competitiveness.